Mass Generation, Neuron Labeling, and 3D Imaging of Minibrains - Govindan, Subashika; Batti, Laura; Osterop, Samira F.; Stoppini, Luc; Roux, Adrien (Frontiers in Bioengineering and Biotechnology, 2021)
Minibrain is a in vitro 3D brain in vitro spheroid model, composed of a mixed population of neurons and glial cells, generated from human iPSC derived neural stem cells. Despite the advances in human 3D in vitro models such as aggregates, spheroids and organoids, there is a lack of labelling and imaging methodologies to characterize these models. In this study, we present a step-by-step methodology to generate human minibrain nurseries and novel strategies to subsequently label projection neurons, perform immunohistochemistry and 3D imaging of the minibrains at large multiplexable scales. To visualize projection neurons, we adapt viral transduction and to visualize the organization of cell types we implement immunohistochemistry. To facilitate 3D imaging of minibrains, we present here pipelines and accessories for one step mounting and clearing suitable for confocal microscopy. The pipelines are specifically designed in such a way that the assays can be multiplexed with ease for large-scale screenings using minibrains and other organoid models. Using the pipeline, we present i. dendrite morphometric properties obtained from 3D neuron morphology reconstructions ii. diversity in neuron morphology and iii. quantified distribution of progenitors and POU3F2 positive neurons in human minibrains.